Age at menarche and lung function: a Mendelian randomization study - Gill, Dipender; Sheehan, Nuala A.; Wielscher, Matthias; Shrine, Nick; Amaral, Andre F. S.; Thompson, John R.; Granell, Raquel; Leynaert, Bénédicte; Real, Francisco Gómez; Hall, Ian P.; Tobin, Martin D.; Auvinen, Juha; et al. (Springer, 2017)
A trend towards earlier menarche in women has been associated with childhood factors (e.g. obesity) and hypothesised environmental exposures (e.g. endocrine disruptors present in household products). Observational evidence has shown detrimental effects of early menarche on various health outcomes including adult lung function, but these might represent spurious associations due to confounding. To address this we used Mendelian randomization where genetic variants are used as proxies for age at menarche, since genetic associations are not affected by classical confounding. We estimated the effects of age at menarche on forced vital capacity (FVC), a proxy for restrictive lung impairment, and ratio of forced expiratory volume in one second to FVC (FEV1/FVC), a measure of airway obstruction, in both adulthood and adolescence. We derived SNP-age at menarche association estimates for 122 variants from a published genome-wide meta-analysis (N = 182,416), with SNP-lung function estimates obtained by meta-analysing three studies of adult women (N = 46,944) and two of adolescent girls (N = 3025). We investigated the impact of departures from the assumption of no pleiotropy through sensitivity analyses. In adult women, in line with previous evidence, we found an effect on restrictive lung impairment with a 24.8 mL increase in FVC per year increase in age at menarche (95% CI 1.8–47.9; p = 0.035); evidence was stronger after excluding potential pleiotropic variants (43.6 mL; 17.2–69.9; p = 0.001). In adolescent girls we found an opposite effect (−56.5 mL; −108.3 to −4.7; p = 0.033), suggesting that the detrimental effect in adulthood may be preceded by a short-term post-pubertal benefit. Our secondary analyses showing results in the same direction in men and boys, in whom age at menarche SNPs have also shown association with sexual development, suggest a role for pubertal timing in general rather than menarche specifically. We found no effect on airway obstruction (FEV1/FVC).